2015
DOI: 10.1073/pnas.1424406112
|View full text |Cite
|
Sign up to set email alerts
|

Signaling between periglomerular cells reveals a bimodal role for GABA in modulating glomerular microcircuitry in the olfactory bulb

Abstract: In the mouse olfactory bulb glomerulus, the GABAergic periglomerular (PG) cells provide a major inhibitory drive within the microcircuit. Here we examine GABAergic synapses between these interneurons. At these synapses, GABA is depolarizing and exerts a bimodal control on excitability. In quiescent cells, activation of GABA A receptors can induce the cells to fire, thereby providing a means for amplification of GABA release in the glomerular microcircuit via GABA-induced GABA release. In contrast, GABA is inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…5HT increases both sEPSC and sIPSC frequency in PGCs and SACs. Moreover, GABA may inhibit, shunt, or even excite glomerular interneurons (Parsa et al 2015). Thus it is not obvious how 5HT might 5HT-evoked responses in SACs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5HT increases both sEPSC and sIPSC frequency in PGCs and SACs. Moreover, GABA may inhibit, shunt, or even excite glomerular interneurons (Parsa et al 2015). Thus it is not obvious how 5HT might 5HT-evoked responses in SACs.…”
Section: Resultsmentioning
confidence: 99%
“…A striking feature of OB circuitry is the prominence of dendrodendritic synapses in addition to classical axodendritic synapses (Hinds 1970;Pinching and Powell 1971a,b;White 1973;Kasowski et al 1999;Kosaka and Kosaka 2011). Dendrodendritic synapses can support action potential-independent neurotransmission between MCs and granule cells (Jahr and Nicoll 1980;Shepherd 1998) and among neurons in the glomerular layer (Aroniadou-Anderjaska et al 1999;Murphy et al 2005;Masurkar and Chen 2012;D'Souza et al 2013;Fekete et al 2014;Liu et al 2015;Parsa et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each cells was stimulated with 5 flashes of light at 20 Hz. Lines connect plots from 309 the same cells.310Functional implications of basal forebrain GABAergic inputs312 Previous studies found that the chloride concentration is high in PG cells and,313 consequently, that GABA is depolarizing(Smith and Jahr, 2002;Parsa et al, 2015). The net 314 impact of GABA is, however, still unclear as one study concluded that GABA inhibits the firing315 of PG cells by shunting excitatory inputs (Smith and Jahr, 2002) whereas the other found 316 that GABA is excitatory and induces the firing of PG cells (Parsa et al, 2015).…”
mentioning
confidence: 99%
“…This bottom-up processing of afferent signals is controlled by modulatory top-down signals, which reach the olfactory bulb from various cortical areas and other brain regions through centrifugal innervation (Matsutani & Yamamoto, 2008;Mouret et al, 2009;Boyd et al, 2012;Nunez-Parra et al, 2013). Cholinergic, serotonergic and adrenergic neuromodulation of bulb circuits have recently been examined in detail (Li & Cleland, 2013;Devore et al, 2014;Eckmeier & Shea, 2014;Rothermel et al, 2014;Schmidt & Strowbridge, 2014;Liu et al, 2015;Parsa et al, 2015;Smith et al, 2015;Brill et al, 2016;Kapoor et al, 2016), and other systems contribute as well (Tobin et al, 2010;Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%